Fatwa Majelis Ulama Indonesia (MUI) tentang Isu Strategis Nasional 2006-2018 dalam Perspektif Maqashid al-Syariah - Hasan Matsum (Al-Ulum, 2023)
This study discusses the Fatwa issued by the Indonesian Ulema Council on National Strategic Issues 2006-2018. The discussion is important because MUI's authority in issuing fatwas is still directly proportional to the diversity of the Muslim community in Indonesia. Knowing the MUI's considerations in issuing a fatwa will certainly influence the appreciation of implementing the fatwa. However, studies on MUI fatwas are still limited to the study of faith and worship, although nationality is also a priority for MUI in giving fatwas. In constructing the results of the study, the authors use the normative law method, so the legal source obtained becomes the secondary data. The results of the study concluded that MUI's consideration in issuing fatwa on National Strategic Issues is hifz al-ummah. Hifz al-ummah is an aspect of al-daruriyah in maqashid al-shariah, namely maintaining the principles of "togetherness" or "national integrity" as a nation, and seeking the benefit of being present in that life.